The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/2358-2936e2020017
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and spatio-temporal distribution of the amphidromous shrimp Macrobrachium olfersii (Caridea: Palaemonidae) along the Ribeira de Iguape River (São Paulo, Brazil)

Abstract: In this study we investigated the distribution of Macrobrachium olfersii (Wiegmann, 1836) along ~150 km of the Ribeira de Iguape river, São Paulo, Brazil. We compared the abundance and spatio-temporal distribution, and checked for differences in size and proportion of each sex in the collections, using two sampling methods. Shrimps were collected monthly at four sites (Eldorado, Sete Barros, Registro, and Iguape), from January to December 2007, using traps and sieves. We obtained a total of 23,818 individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 63 publications
1
0
0
Order By: Relevance
“…The concentration of juveniles in the lower reaches of the Fitzroy River strongly suggests an amphidromous life history. A similar pattern was found in the perennial Daly River, some 740‐km north‐east of the Fitzroy River (Novak et al, 2015) and has been reported for other amphidromous Macrobrachium species (Bauer & Delahoussaye, 2008; Novak, Bayliss, Crook, et al, 2017; Ribeiro et al, 2020). Amphidromy in the Fitzroy River is also supported by photographic documentation of small shrimp migrating upstream en masse at the Camballin Barrage during the late wet season (mid‐February in 2019 and early April in 2020).…”
Section: Discussionsupporting
confidence: 78%
“…The concentration of juveniles in the lower reaches of the Fitzroy River strongly suggests an amphidromous life history. A similar pattern was found in the perennial Daly River, some 740‐km north‐east of the Fitzroy River (Novak et al, 2015) and has been reported for other amphidromous Macrobrachium species (Bauer & Delahoussaye, 2008; Novak, Bayliss, Crook, et al, 2017; Ribeiro et al, 2020). Amphidromy in the Fitzroy River is also supported by photographic documentation of small shrimp migrating upstream en masse at the Camballin Barrage during the late wet season (mid‐February in 2019 and early April in 2020).…”
Section: Discussionsupporting
confidence: 78%
“…1). According to Ribeiro et al (2020), the river margins are similar in these four regions, surrounded by pastures and banana plantations. The vegetation on the banks mainly comprises grasses (Brachiaria subquadripara, Brachiara platyphylla, and Panicum dichotomiflorum).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…1). We followed the collection method proposed by Ribeiro et al (2020). In each area, samples were obtained using traps and sieves in two locations, 2 km apart.…”
Section: Description Of the Study Areamentioning
confidence: 99%
See 2 more Smart Citations